Systematic selection of modified aptamer pairs for diagnostic sandwich assays. (March 2014) - Ochsner, Urs A.; Green, Louis S.; Gold, Larry; Janjic, Nebojsa
Protein diagnostic applications typically require pairs of analyte-specific reagents for capture and detection. We developed methods for the systematic isolation of slow off-rate modified aptamer (SOMAmer) reagents that bind to different epitopes and allow efficient pair-wise screening of multiple ligands. SOMAmers were generated via a second systematic evolution of ligands by exponential enrichment (SELEX), using complexes of target proteins with a primary, non-amplifiable SOMAmer and employing different modified nucleotides (e.g., naphthylmethyl- or tryptaminocarbonyl-dU) to favor alternate binding epitopes. Non-competing binding of primary and secondary SOMAmers was tested in radiolabel competition and sandwich binding assays. Multiplexed high-throughput screening for sandwich pairs utilized the Luminex platform, with primary SOMAmers as capture agents attached to different types of LumAvidin beads, which were then pooled for testing the secondary SOMAmers individually as detection agents. Functional SOMAmer pairs were obtained for Clostridium difficile binary toxin (CdtA) and for a panel of human proteins (ANGPT2, TSP2, CRDL1, MATN2, GPVI, C7, PLG) that had been previously identified as promising markers for cardiovascular risk. The equilibrium dissociation constants (Kd values) ranged from 0.02–2.7 nM, and the detection limits were in the low picomolar range for these proteins in SOMAmer sandwich assays. These results indicate that SOMAmer pairs hold promise for the development of rapid tests or specific diagnostic panels.